Histone methyltransferase Dot1L inhibits pancreatic cancer cell apoptosis by promoting NUPR1 expression. Issue 3 (March 2022) - Shan, Lin; Hao, Chen; Jun, Zheng; Qinghe, Cai
Objective: To explore functions of the histone H3 lysine 79 (K79) methyltransferase Dot1L in the development of pancreatic cancer and evaluate the possibility of targeting Dot1L to inhibit pancreatic cancer progression. Methods: Patient samples were used to detect differences in Dot1L expression between tumor and adjacent tissues and to determine correlations between Dot1L expression in patients with different stages of pancreatic cancer. Lentiviral-mediated knockdown of Dot1L expression and flow cytometry were used to detect apoptosis in pancreatic cancer lacking Dot1L expression; chromatin immunoprecipitation and quantitative PCR were used to detect downstream target genes of Dot1L. Results: We show that Dot1L is highly expressed in pancreatic cancer, and that its expression is related to pancreatic cancer stage. Knocking down Dot1L significantly promoted apoptosis in pancreatic cancer cells, while overexpressing Dot1L inhibited apoptosis. Mechanistically, Dot1L regulated apoptosis in pancreatic cancer cells by promoting NUPR1 expression. The enriched H3K79 trimethylation in the transcription initiation region of NUPR1 promoted its expression. Overexpressing NUPR1 inhibited the pancreatic cancer cell apoptosis caused by Dot1L knockdown. Conclusions: Dot1L inhibits pancreatic cancer cell apoptosis by targeting NUPR1; thus, Dot1L is a promising target for pancreatic cancer treatment.